Elaboración del diagnóstico y recomendaciones al proceso de gestión de adquisiciones difundido por Colombia Compra Eficiente, enfocado en el sector de infraestructura vial en Colombia. (2018)
The present work of degree, search with the elaboration of the diagnostic and recommendations to the procurement management process diffused by Colombia Compra Eficiente, focused on the road infrastructure sector in Colombia, making a comparative analysis of the differences and similarities presented by the documents, guides and type manuals, disseminated by the National Agency of Public Procurement - Colombia Compra Eficiente -, and the guidelines described by the PMI in the PMBOK guide 6th edition related to the management of acquisitions. Evidencing findings and recommendations that allow the use of this document as an opportunity to improve public procurement processes in Colombia.